The antibacterial activity of a photoactivatable diarylacetylene against Gram-positive bacteria - Waite, Ryan; Adams, Candace T.; Chisholm, David R.; Sims, C. H. Cole; Hughes, Joshua G.; Dias, Eva; White, Emily A.; Welsby, Kathryn; Botchway, Stanley W.; Whiting, Andrew; Sharples, Gary J.; Ambler, Carrie A. (Frontiers in Microbiology, 2023)
The emergence of antibiotic resistance is a growing threat to human health, and therefore, alternatives to existing compounds are urgently needed. In this context, a novel fluorescent photoactivatable diarylacetylene has been identified and characterized for its antibacterial activity, which preferentially eliminates Gram-positive over Gram-negative bacteria. Experiments confirmed that the Gram-negative lipopolysaccharide-rich outer surface is responsible for tolerance, as strains with reduced outer membrane integrity showed increased susceptibility. Additionally, bacteria deficient in oxidative damage repair pathways also displayed enhanced sensitivity, confirming that reactive oxygen species production is the mechanism of antibacterial activity. This new diarylacetylene shows promise as an antibacterial agent against Gram-positive bacteria that can be activated in situ, potentially for the treatment of skin infections.